An Abbreviated Irmologion - Kappanadze, Paul (Journal of the International Society for Orthodox Music, 2020)
This paper describes the process behind the on-going work at St Tikhon of Zadonsk Monastery (South Canaan, Pennsylvania) to produce an abbreviated and practical Heirmologion to meet the needs of English-speaking monasteries and parishes within the tradition of the Russian Orthodox Church. The Heirmologion is unique among liturgical books in that it contains a single genre of hymn: the heirmos (Gr. Εἱρμὸς, Slv. Ирмoсъ), that is, the hymn at the beginning of each of the nine odes of a canon, most often sung at Matins and Compline. There does not, as yet, exist a comprehensive or widely available anthology of heirmoi in the English language. The music staff at St Tikhon’s Monastery, therefore, is endeavouring to fill this gap in the library of liturgical books in English. The compilation of an abbreviated Heirmologion in English was first attempted in 2011, but only the text of the Tone 1 heirmoi from the Octoechos was compiled. Four years later the idea for an English Heirmologion was revived by the need for such a collection at St Tikhon’s Monastery. Theodore Heckman, former music director at St Tikhon’s Seminary, contributed a considerable amount of work by notating heirmoi from the Sunday Octoechos, Menaion, Triodion, and Pentecostarion, primarily for mixed choirs. Archimandrite Sergius, the monastery’s current abbot and former music director, has taken further steps in compiling the text for heirmoi from the weekday Octoechos canons. Until 2017, therefore, the monastic male choir either sang from old mixed choir scores or from text, but there was no standard collection of notated heirmoi that was adaptable to the small choir’s daily needs. With consideration for these needs the first part of the present collection was submitted as a senior honours project, titled “An Abbreviated Irmologion: The Octoechos,” in 2017 at St Tikhon’s Seminary by Paul Kappanadze. It contained the heirmoi for the canons in the Octoechos and two commonly used canons to the Theotokos. This initial anthology has since been expanded as heirmoi from the canons of the Festal Menaion, Lenten Triodion, and Pentecostarion have been and continue to be added. Although this is an on-going project, the entire process has been informed by choices made at its inception: namely, decisions about the contents, the texts to be used, the chant melodies, notation, and how to organize the contents.